2003
DOI: 10.1139/s03-046
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic treatment of maize-processing wastewater (nejayote) in a single-stream multi-stage bioreactor

Abstract: The manufacturing processes of tortillas, corn chips, tortilla chips, and related products yield a liquid waste called nejayote. This waste causes serious pollution problems since its chemical oxygen demand is very high, from 25000 to 30000 ppm. To reduce the pollution potential of this effluent, the use of a cascade of three continuous flow bioreactors-in-series is proposed in this work. When nejayote was supplemented with KH2PO4 and (NH4)2SO4, at COD:KH2PO4 and COD:(NH4)2SO4 ratios of 87 and 26, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 6 publications
0
21
0
2
Order By: Relevance
“…A major type of waste water in Mexico is waste waters resulting from nixtamalization of maize (Zea mays). A production of 600 Ton maize per day produces between 1500 and 2000 m 3 of the waste water, the monthly volume generated in Mexico is about of 1.2 million m 3 [1]. The latter process is carried out as a pretreatment of the maize grain in order to make it more amenable (during its postprocessing) to preparation of flour, masa, tortillas, and other food products [2].…”
Section: Introductionmentioning
confidence: 99%
“…A major type of waste water in Mexico is waste waters resulting from nixtamalization of maize (Zea mays). A production of 600 Ton maize per day produces between 1500 and 2000 m 3 of the waste water, the monthly volume generated in Mexico is about of 1.2 million m 3 [1]. The latter process is carried out as a pretreatment of the maize grain in order to make it more amenable (during its postprocessing) to preparation of flour, masa, tortillas, and other food products [2].…”
Section: Introductionmentioning
confidence: 99%
“…COD and BOD values of wastewater can be reduced using aerobic (Pedroza‐Islas & Durán de Bazúa, ; Salmerón‐Alcocer et al, ) and anaerobic reactors (Civit, Durán de Bazúa, Engelmann, González, & Hartmann, ; Durán de Bazúa, Sanchez‐Tovar, Hernandez‐Morales, & Bernal‐Gonzalez, ). It has been reported that usage of one of the anaerobic and aerobic systems will be economical for the corn industries with daily 2,500 m 3 or more wastewater.…”
Section: Treatment Processesmentioning
confidence: 99%
“…Traditional maize is lime-cooked in clay pots over a fire, followed by steeping for 8-16 h (generally overnight), the supernatant called maize wastewater or commonly known as "nejayote", derived from the Nahuatl word meaning "lime broth ashes" is discarded and then the nixtamal is hand-washed. Nixtamal is ground into a fine masa with a stone grinder called metate and then hand-molded, patted or pressed into disks, which are baked on both sides on a hot griddle [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nejayote is considered an environmental pollutant because it is an alkaline wastewater, with high chemical and biological oxygen demand [2,9]. Due to the presence of lime in the process, the pH of the wastewater is very high (12)(13)(14), with a high temperature between 40 and 70°C), containing suspended solids (corn husks and broken grains) and a very high portion of dissolved material from the alkaline hydrolysis of corn components [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation